Angry young men and women: How to understand reactions to strong supervisory behavior. Issue 5 (11th July 2016) - Linacre, Simon
Abstract : Purpose: Reviews the latest management developments across the globe and pinpoints practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Portrayals of superiors in film or on television are rarely positive. Think about it for a second. The cliche of the boss or supervisor is of an aggressive male, barking orders at employees, showing barely any humanity and never satisfied by anything his charges do for him. Alternatively, there is the stereotypically "hard-assed" woman boss who is similarly unyielding or sometimes the other end of the spectrum is used, and a boss is shown to be slightly deranged or so ineffectual as to be rendered irrelevant by their subordinates. Practical Implications: Provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.